Analisis Efektivitas Mesin pada Proses Produksi Cryogenic Pipe Shoe di PT Binder Indonesia Menggunakan Metode Overall Equipment Effectiveness (OEE) - Simarmata, Leo Tubagus; Widya, Adi Rusdi; Prasetya, Dwi Indra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes machine effectiveness in Cryogenic Pipe Shoe production at PT Binder Indonesia using the Overall Equipment Effectiveness (OEE) method. Data were collected through observation, interviews, documentation, and literature review between April and June 2024. Results show OEE improved from 86.8% to 92.1%, surpassing the JIPM standard (85%). The main issue reducing effectiveness was downtime from technical failures, particularly in availability and performance. Root cause analysis revealed gaps in preventive maintenance, operator self-inspection skills, and post-maintenance quality control. The study recommends systematic preventive maintenance scheduling, operator training, and stronger quality control to enhance productivity and minimize delivery delays.